(untitled) (Desenvolvimento em Questão, 2023)
The work aimed to develop the methodological bases of the Human and Intellectual Dimension Index of Territorial Heritage (IDHI), operationalizing the variables that compose it from a scale. The methodology was based on the use and adaptation of the Likert Scale, with five points, parameterizing the indicators on human and intellectual development that integrate this dimension of territorial development. As a result, we have an index that can be applied to measure the human and intellectual dimension of the territorial heritage in a scientific and multifaceted way, but at the same time being flexible and adaptable to the empirical realities and specificities of the territories in which it will be used. This index can be used by researchers from different territories and by managers of public policies who are concerned with measuring the territorial heritage in its human and intellectual aspects.